2021
DOI: 10.3390/nu13072433
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Food Label Comprehension among Libyan Migrants in Australia

Abstract: Food security among migrants and refugees remains an international public health issue. However, research among ethnic minorities in Australia is relatively low. This study explored the factors that influence the understanding of food labelling and food insecurity among Libyan migrants in Australia. An online survey was completed by 271 Libyan migrant families. Data collection included the 18-item US Household Food Security Survey Module (for food security) and a question from the Food Standards Australia New … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…A systematic review of studies with migrants and refugees from the Middle East and North Africa living in high-income countries found that the prevalence of FI ranged from 40 % to 71 % (10) . Other studies found that among Lebanese migrants living in Australia, the prevalence of FI was 72·7 % (35) , whereas Haitian migrants residing in Chile had a prevalence of 78 % (36) . In the USA, another systematic review on migrants and seasonal agricultural workers showed that the prevalence of FI varied depending on the region where the research was carried out.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of studies with migrants and refugees from the Middle East and North Africa living in high-income countries found that the prevalence of FI ranged from 40 % to 71 % (10) . Other studies found that among Lebanese migrants living in Australia, the prevalence of FI was 72·7 % (35) , whereas Haitian migrants residing in Chile had a prevalence of 78 % (36) . In the USA, another systematic review on migrants and seasonal agricultural workers showed that the prevalence of FI varied depending on the region where the research was carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Income is a distinct barrier to food security among migrants [33,54] and general population subgroups [57]. Interviewees in our study adopted various approaches to try and overcome this barrier.…”
Section: Discussionmentioning
confidence: 99%
“…It was noted that while many migrants were highly educated, they were still food insecure [33]. They were highly literate but struggled with some aspects of labelling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations